ClC-c regulates the proliferation of intestinal stem cells via the EGFR signalling pathway in Drosophila. - Huang, J.; Sheng, X.; Zhuo, Z.; Xiao, D.; Wu, K.; Wan, G.; Chen, H. (Cell proliferation, 2022)
Adult stem cells uphold a delicate balance between quiescent and active states, which is crucial for tissue homeostasis. Whereas many signalling pathways that regulate epithelial stem cells have been reported, many regulators remain unidentified. Flies were used to generate tissue-specific gene knockdown and gene knockout. qRT-PCR was used to assess the relative mRNA levels. Immunofluorescence was used to determine protein localization and expression patterns. Clonal analyses were used to observe the phenotype. RNA-seq was used to screen downstream mechanisms. Here, we report a member of the chloride channel family, ClC-c, which is specifically expressed in Drosophila intestinal stem/progenitor cells and regulates intestinal stem cell (ISC) proliferation under physiological conditions and upon tissue damage. Mechanistically, we found that the ISC loss induced by the depletion of ClC-c in intestinal stem/progenitor cells is due to inhibition of the EGFR signalling pathway. Our findings reveal an ISC-specific function of ClC-c in regulating stem cell maintenance and proliferation, thereby providing new insights into the functional links among the chloride channel family, ISC proliferation and tissue homeostasis.